Malaysia : Financial Sector Assessment Program Stress Testing the Malaysian and Labuan IBFC Banking Sectors-Technical Note. (IMF Staff Country Reports; Country Report, 2014)
This paper summarizes the stress tests (ST) undertaken for the Malaysian banking system as part of the Financial Sector Assessment Program (FSAP). All banks were subject to solvency, liquidity and contagion tests in the macroeconomic stress testing set-up. The solvency tests assessed the resilience of the Malaysian banking system under three macroeconomic scenarios from 2012 to 2016. Single year bottom up (BU) sensitivity tests for Malaysian banks covered various single-factor credit and market risk shocks. A multi-factor BU sensitivity liquidity test was also carried out by participating banks and extended to not only key onshore banks but covered some Labuan entities and overseas subsidiaries. The findings suggest that the onshore banking system in Malaysia has substantial capital buffers to absorb credit losses on its credit risk exposures. Conventional banks can benefit from buffers provided by significant income as a first line of defense against credit losses. Some larger domestic banks benefit from income in terms of strong revenues from domestic operations as well as potential income from overseas operations.